The Influence of Change Management, Financial Compensation, Work Discipline on the Performance of University Cirebon - Mohammad Faizal Akmal; Ivan Purnama; Edy Hartono (Universitas KH. Abdul Chalim Mojokerto, 2025)
Lecturers in a university play an important role because their performance contributes to the progress of the university. Universities demand that lecturers have a high work spirit, as well as be resilient in working with high competence, and high work discipline, but unfortunately, college management pays less attention to lecturer performance issues. Therefore, this study was conducted to address the performance of lecturers of private universities in Cirebon. This study aims to determine the Effect of Change Management, Financial Compensation, and Work Discipline on Lecturer Performance in Private Universities in Cirebon. The type of research used in this study is a quantitative method with an associative research approach. Data collection through questionnaires. Data collection techniques using questionnaires and using statement indicators with a Likert scale of 1-5. The population in this study was lecturers in Cirebon Private Universities, as many as 396, and a sample of 199. The results of the study concluded that Change Management, Financial Compensation, and Work Discipline affect Lecturer Performance.